The impact of internal control, cultural control, incentives, and work discipline on employee performance (Case study in PT Lestari Jaya Raya) - Luis Fernando; Dwi Asih Surjandari (Annals of Management and Organization Research, 2021)
Purpose: The goal of this research was to see how Internal Control, Cultural Control, Incentives, and work discipline affected Employee Performance at PT Lestari Jaya Raya. Research methodology: The type of this research is a quantitative descriptive study that used a questionnaire to collect data. This study has a population, they were all employees of PT Lestari Jaya Raya with the sample in this study were office staff of 53 people. Results: The results of this study showed that Cultural Control and Work Discipline had a positive impact on Employee Performance. Meanwhile, Internal Control and Incentives have no impact on Employee Performance. This means that the greater the Cultural Control and Work Discipline of the employee, the better the resulting Employee Performance Limitations: This study is limited to the office staff of PT Lestari Jaya Raya so it has not described the overall condition of the employees of PT Lestari Jaya Raya which consists of office staff and operational staff. Contribution: The results of this study are intended to be beneficial as management input, especially in the field of management accounting related to Employee Performance.